INFLUENCE OF TRADE AND ECONOMIC DEVELOPMENT OF TURKESTAN ON THE SOCIAL LIFE OF THE PEOPLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides information about the creation of Russian banks and branches in Turkestan at the beginning of the 20th century, the close connection of Russian banks with international banks, the management of the State Bank and the Russian-Asian Bank, as well as the impact of the development of trade and economics in Turkestan on the social life of the people.